2021
DOI: 10.1111/jonm.13296
|View full text |Cite
|
Sign up to set email alerts
|

New graduate nurses' satisfaction, adaptation and intention to leave in their first year: A descriptive study

Abstract: Aim To determine the factors affecting the professional and institutional satisfaction of new graduate nurses in their first year of work, their adaptation process and their intentions of leaving the nursing profession. Background The number of new graduates has been increasing in the global labour force, yet a significant proportion of them have left their profession. The first year in the nursing profession is particularly stressful and challenging for new graduate nurses. Methods The study was conducted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 18 publications
1
41
1
3
Order By: Relevance
“…In this study, the mean age of NGNs was 23.4 years, and about three-quarters of them were 24 years old or younger. Studies with a sample of new graduates in Turkey reported that the mean age was approximately 23 years, 10,32 and more than half of them were between the years of 21 and 24. 33 NGNs in this study were reported as younger than studies in United States, 4 South Korea, 5 Canada, 11 and Finland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the mean age of NGNs was 23.4 years, and about three-quarters of them were 24 years old or younger. Studies with a sample of new graduates in Turkey reported that the mean age was approximately 23 years, 10,32 and more than half of them were between the years of 21 and 24. 33 NGNs in this study were reported as younger than studies in United States, 4 South Korea, 5 Canada, 11 and Finland.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Turkey by Ulupinar and Aydogan, approximately 43% of NGNs reported intentions to leave the profession. 32 The turnover score of NGNs was reported in Canada 11 and South Korea, 44 as 2.47 and 3.24 out of 5, respectively. Medium to high turnover intention among NGNs is considered a major concern in healthcare systems because of reflecting the near future turnover rate.…”
Section: Discussionmentioning
confidence: 99%
“…The program purpose was to enhance clinical competence and reduce turnover, yet nurse leaders know that NGN continued to struggle. NGNs report that high workload, inadequate skills and knowledge, and stress from patient, family, and team communication contribute to turnover 6 . NGN stay when they feel supported by other nursing staff and valued by members of the team and have the ability to contribute to the team 7 …”
Section: Changing Timesmentioning
confidence: 99%
“…NGNs report that high workload, inadequate skills and knowledge, and stress from patient, family, and team communication contribute to turnover. 6 NGN stay when they feel supported by other nursing staff and valued by members of the team and have the ability to contribute to the team. 7 The Evolution of NGN Transition Into Practice…”
Section: Changing Timesmentioning
confidence: 99%
“…Ulupınar & Aydogan [39] found that 42.5% (n=428) of new graduate nurses in the rst years of their career had considered leaving nursing. In Sweden, 10-20% of fresh graduates have considered leaving the profession [15].…”
Section: Independent Variablesmentioning
confidence: 99%